Synthesis of Bamboo-based Activated Carbon through Physico-chemical Activation for Coal-runoff Wastewater Treatment - Anggi Saputra; Oktaf Rina; Rahmat Hidayat; Murni Fitria; Syahdilla Anggiva Akhni; Ajis Purnomo; Aang Haryadi (Universitas Islam Indonesia, 2023)
Bamboo-based activated carbon (BAC) has been successfully synthesized through a physico-chemical technique. The characteristics of BAC were investigated using Scanning Electron Microscopy (SEM), Fourier Transform Infra-Red (FTIR), and X-Ray Diffraction (XRD). Evaluating BAC performance on coal-runoff wastewater was carried out by varying contact times and adding low-level alum on remediation of pH and Total Suspended Solid (TSS). The results confirm that BAC performs well in stabilizing pH, indicated by the neutral pH, after 10 minutes of interaction. The TSS with BAC treatment and 1% BAC-Alum combination reduced the TSS value from 880 mg/L to levels below the threshold for wastewater quality standards, 387 mg/L and 73 mg/L, respectively. This combination can be an alternative coal-runoff wastewater treatment technique for better environmental quality.